Factors Influencing Brucellosis Preventive Behaviors among Marginalized Iranian Women: An Application of the Health Belief Model - Majid Barati; Rezvan Shayghan Zahed; Marjan Bakhtiari; Yadollah Fathi; Maryam Afshari; Zahra Taheri-Kharameh (The Scientific World Journal)
Background. Brucellosis is still a serious public health threat in developing countries, especially in Iran. Brucellosis is an endemic disease in Iran and risk factors increasing its broadcast are prevalent. This study investigated factors influencing brucellosis preventive behaviors amongst marginalized women in Hamadan city, Iran, using the health belief model (HBM). Methods. In this cross-sectional study, 289 women living in marginal areas were considered from April until May 2018. Via cluster random sampling methods, comprehensive health services where women get health care were selected. Each woman in the selected comprehensive health services was then enrolled by the simple random sampling method. Data were gathered from a face-to-face interview via a questionnaire. Results. Most women had a history of using nonpasteurized dairy products (86.2%). Most women (64.7%) boiled the milk for 3–5 minutes. 61.2% of women put the cheese in a salt-water solution. The results showed that one unit rise in the scores of knowledge, self-efficacy, and cues to action resulted in an increase in the mean score of the protective behavior by 0.189, 209, and 0.150, respectively. Conclusion. The HBM was a helpful model in predicting the influential elements in brucellosis preventive behaviors. Also, recognized effective factors should be taken into account when designing interventions.